2009
DOI: 10.1016/j.ejphar.2009.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Two allelic isoforms of the serotonin transporter from Schistosoma mansoni display electrogenic transport and high selectivity for serotonin

Abstract: The human blood fluke Schistosoma mansoni is the primary cause of schistosomiasis, a debilitating disease that affects 200 million individuals in over 70 countries. The biogenic amine serotonin is essential for the survival of the parasite and serotonergic proteins are potential novel drug targets for treating schistosomiasis. Heterologous expression of the two cDNAs in mammalian cells resulted in saturable, sodiumdependent serotonin transport activity with an apparent affinity for serotonin comparable to that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Similar to what we found in the smSERT [12], we identified two different SmDAT isoforms that differed in two amino acids located in the protein’s predicted intracellular N-terminal. In isoform A, residue 54 is a lysine and residue 59 is an asparagine.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Similar to what we found in the smSERT [12], we identified two different SmDAT isoforms that differed in two amino acids located in the protein’s predicted intracellular N-terminal. In isoform A, residue 54 is a lysine and residue 59 is an asparagine.…”
Section: Resultssupporting
confidence: 83%
“…The other putative catecholamine transporter although with significantly lower homology was the Smp_193800/ XP_002571308.1. Other transporter proteins were identified in this search and homology analyses suggested that they were the recently characterized serotonin transporter [12](smSERT) (Smp_157420/XP_002577786.1; Smp_157430/XP_002577787.1), glycine transporters (Smp_131890/XP_002569602.1; Smp_028690/XP_002574310.1), and creatine/taurine transporters (Smp_160360/XP_002578233.1; Smp_078930/XP_002579022.1; Smp_143800/XP_002575336.1)…”
Section: Resultsmentioning
confidence: 99%
“…Amphetamine derivatives such as fenfluramine, p-chloroamphetamine (PCA) and 3,4 –methylenedioxymethampetamine (MDMA or “Ecstasy”) are substrates for SERT (Rudnick & Wall, 1992). SERT in turn affords an access pathway to the cytoplasm for these drugs, where interactions with SERT and VMATs can, in concert, lead to nonvesicular 5-HT efflux (Fontana et al, 2009; Gobbi et al, 1997; Hilber et al, 2005; Seidel et al, 2005). SERT-knockout mice have provided unequivocal evidence that SERT is important for synaptic 5-HT clearance, SSRI recognition, MDMA induced hyperactivity and may contribute to the reinforcing effect of cocaine.…”
Section: The Serotonin Transporter and Its Functional Significancementioning
confidence: 99%
“…The additional finding that a serotonin receptor agonist and a serotonin ligand also block transformation is consistant with this hypothesis in that both of these compounds activate the serotonin receptor leading to the activation of ADCY. Previous studies in S. mansoni have demonstrated that citalopram and clomipramine function as selective serotonin reuptake inhibitors by inhibiting the S. mansoni 5-HT serotonin transporter SmSERT in a heterologous expression system (Patocka and Ribeiro, 2007; Fontana et al, 2009). Although Boyle et al (2003) did not detect serotonin transporter activity in miracidia they were only examining the uptake of exogenous 5-HT and would have likely missed endogenous 5-HT transport.…”
Section: Discussionmentioning
confidence: 99%